2018
DOI: 10.1097/dcr.0000000000000976
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Ureteral Catheters for Colectomy: A National Surgical Quality Improvement Program-Based Analysis

Abstract: Here, prophylactic ureteral catheters were used in 4.9% of colectomies and most commonly for diverticulitis. On multivariate analysis, prophylactic catheter placement was associated with a lower rate of ureteral injury. Additional research is needed to delineate patient populations most likely to benefit from prophylactic ureteral stent placement. See Video Abstract at http://links.lww.com/DCR/A482.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 21 publications
1
29
0
1
Order By: Relevance
“…28,29 According to recent literature, left ureteral stent are used in 4.9% patients submitted to colorectal resections, and the rate is constantly increasing. 30 Nevertheless, data are controversial and a recent systematic review concluded that there is insufficient evidence to conclude that stents decrease ureteric injury or increase intraoperative ureteric detection. 31 Our ureteric stent placement rate is lower (2.5%) when compared to the available literature (up to 16% for diverticular disease), 32 The limitations of this study are its retrospective design, the absence of a comparative group, and the relatively small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 According to recent literature, left ureteral stent are used in 4.9% patients submitted to colorectal resections, and the rate is constantly increasing. 30 Nevertheless, data are controversial and a recent systematic review concluded that there is insufficient evidence to conclude that stents decrease ureteric injury or increase intraoperative ureteric detection. 31 Our ureteric stent placement rate is lower (2.5%) when compared to the available literature (up to 16% for diverticular disease), 32 The limitations of this study are its retrospective design, the absence of a comparative group, and the relatively small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…The pros and cons of this endoscopic intervention should be discussed with the patients. When the ureter has not been damaged during the surgery, these stents can be immediately removed or left overnight [33][34][35].…”
Section: Non-urological Procedures Involving Ureteral Dissectionmentioning
confidence: 99%
“…Available evidence suggests that routine ureteral stenting in surgery for diverticular disease is associated with a longer operative time, longer length of stay, and higher costs [158][159][160]. Analysis of the protective impact of ureteral stents against ureteral injury in the literature is always confounded by selection bias, as higher-risk patients are more likely to receive stents.…”
Section: Ureteral Stentsmentioning
confidence: 99%